Trimethyltin chloride exposure induces apoptosis and necrosis and impairs islet function through autophagic interference - Yanhe Zhang; Jie Cui; Kan Li; Shuang Xu; Hang Yin; Shu Li; Xue-jiao Gao (Ecotoxicology and Environmental Safety, 2023)
Trimethyltin chloride (TMT) is a highly toxic organotin compound often used in plastic heat stabilizers, chemical pesticides, and wood preservatives. TMT accumulates mainly through the environment and food chain. Exposure to organotin compounds is associated with disorders of glucolipid metabolism and obesity. The mechanism by which TMT damages pancreatic tissue is unclear. For this purpose, a subacute exposure model of TMT was designed for this experiment to study the mechanism of damage by TMT on islet. The fasting blood glucose and blood lipid content of mice exposed to TMT were significantly increased. Histopathological and ultrastructural observation and analysis showed that the TMT-exposed group had inflammatory cell infiltration and necrosis. Then, mouse pancreatic islet tumour cells (MIN-6) were treated with TMT. Autophagy levels were detected by fluorescence microscopy. Real-time quantitative polymerase chain reaction and Western blotting were used for verification. A large amount of autophagy occurred at a low concentration of TMT but stagnated at a high concentration. Excessive autophagy activates apoptosis when exposed to low levels of TMT. With the increase in TMT concentration, the expression of necrosis-related genes increased. Taken together, different concentrations of TMT induced apoptosis and necrosis through autophagy disturbance. TMT impairs pancreatic (islet β cell) function.